Peculiarities of suffix wordbuilding of the names of the fishes in Ukrainian dialects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The author studies productive wordbuilding models, which unite the names of the fishes in Ukrainian dialects. The wordbuilding affixes semantics, their shades of meaning, synonimic and opposite relations their areas are studied.
Keywords: wordbuilding model; suffix; fishes names; semantics